The Effect of Self-Concept, Learning Habit, and Motive of Achievement toward the Learning Achievement - Pamujo, Pamujo (EDUCARE, 2014)
ABSTRACT: This research is aimed at finding out the effect of self-concept, learning habit, and achievement motivation toward the students learning achievement at the six-grade of Elementary Schools in the Kebasen District of the Banyumas Regency in Central Java, Indonesia, both individually and wholly. This research belongs to ex-post facto type with descriptive-quantitative approach. The sample, a cluster one, was 20% of the population which was 150 students of the six grade or two classes of each category. The data for the learnersâ self-concept, learning habit, and achievement motivation was collected through questionnaire based on Likert scale with four options of answer, while that of the students learning achievement was taken from the list of scores of the National Examination. The correlation between the independent and dependent variable was analyzed using correlational statistics and multiple regression. Hypothesis was tested at the level of significance with Î± = 0.05. The result was that the mean score of the self concept was 3.175, the learning habit 3.311, and the achievement motivation 2.973, which belong to the category âhigh, very high, and highâ respectively. The mean score of the learning achievement was 22.09, which was categorized as âfairâ. Individually, the self-concept (t = 3.512, p = 0.001), learning habit (t = 2.603, p = 0.010), and achievement motivation (t = 2.679, 0 = 0.008) gave positive and significant effect toward learning achievement. Simultaneously, the three variables X1 (the self-concept), X2 (the learning habit), and X3 (the achievement motive) showed significant effect, the F count being 12.789 with p at 0.000.KEY WORDS: Self-concept, learning habit, motive of achievement, learning achievement, elementary schools, and national examination.About the Author: Pamujo, M.Pd. is a Lecturer at Study Program of Elementary-School Teacher Education UMP (Muhammadiyah University of Purwokerto), Jalan Raya Dukuhwaluh, P.O. Box 202, Purwokerto 53182, Central Java, Indonesia. He can be reached at: pam@ump.ac.idHow to cite this article? Pamujo. (2014). âThe Effect of Self-Concept, Learning Habit, and Motive of Achievement toward the Learning Achievementâ in EDUCARE: International Journal for Educational Studies, Vol.7(1) August, pp.19-26. Bandung, Indonesia: Minda Masagi Press and UMP Purwokerto, ISSN 1979-7877. Chronicle of the article: Accepted (July 23, 2014); Revised (July 30, 2014); and Published (August 17, 2014).